2002
DOI: 10.1080/014608602753504829
|View full text |Cite
|
Sign up to set email alerts
|

Medically Fragile Children: An Integrative Review of the Literature and Recommendations for Future Research

Abstract: The literature related to medically fragile children (MFC) is analyzed, and a model is generated to improve quality of care and cost effectiveness. The sources of stress for families include home care professionals, respite care, financial concerns, and limited community resources. Children cared for in hospitals often experience less than desirable quality outcomes. Community-based pediatric extended care facilities may be a means of reducing family stress, improving physiologic and developmental outcomes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…Many family members who care for their children at home report significant physical, emotional, social, and financial burdens. 3 The National Survey of Children with Special Health Care Needs found that a significant percentage of families provide greater than 21 hours per week of health care at home and spend upward of 11 hours per week on care coordination. 1 This survey also reported that 25% of families curtail work or leave their jobs to care for their children.…”
Section: Introductionmentioning
confidence: 99%
“…Many family members who care for their children at home report significant physical, emotional, social, and financial burdens. 3 The National Survey of Children with Special Health Care Needs found that a significant percentage of families provide greater than 21 hours per week of health care at home and spend upward of 11 hours per week on care coordination. 1 This survey also reported that 25% of families curtail work or leave their jobs to care for their children.…”
Section: Introductionmentioning
confidence: 99%
“…Published critical reviews on various aspects of family care for children in Europe conclude that families are emotionally, physically, and financially stressed, often anxious about their child's condition or the complications that may develop and fearful of potential emergency situations that may occur (Hastings & Taunt, 2002;Harrigan, et al, 2002). For instance, Harrigan and associates (2002) found that families need extensive, continuous services, including education, emotional support, skilled supportive respite care and financial assistance to be able to care for their children and wards.…”
Section: Robert B Kuganab Lem the Social Consequences Of Raising Medmentioning
confidence: 99%
“…The complexity and continuous nature of the conditions of medically fragile children and the high level of skills their care demands, differentiates children who are medically fragile and developmentally challenged from the general population of children (Harrigan, 2002; Kirk, 1998). The complex and continuous care that such children need put extra stress on parents, especially mothers, thus limiting their participation in social activities.…”
Section: Robert B Kuganab Lem the Social Consequences Of Raising Medmentioning
confidence: 99%
“…Previous studies have included descriptions of the technology required by medically fragile children and adolescents. The technology requirements have varied from intermittent to continuous technology needs with nurse dependent care (Earle et al, 2006;Haley & Ratliffe, 2006;Harrigan et al, 2002;Heaton et al, 2005;Rehm & Bradley, 2005;Rehm & Rohr, 2002). Medically fragile adolescents who require respiratory assistance may require respiratory technologies in addition to several other technologies, reflecting a medically fragile population with multiple technology needs.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, various names are used to reflect children and adolescents who require assistance from medical technology. These terms include medically fragile (Haley & Ratliffe, 2006;Harrigan, Ratliffe, Patrinos, & Tse, 2002), technology-dependent (Cohen, 1999;Earle, Rennick, Carnevale, & Davis, 2006;Carnevale, Alexander, Davis, Rennick, & Troini, 2006;Heaton, Noyes, Sloper, & Shah, 2005;Montagnino & Mauricio, 2004), medically fragile/technology-dependent (Rehm & Rohr, 2002), medically fragile/developmentally delayed (Rehm & Bradley, 2006;Rehm & Bradley, 2005), children with complex chronic health conditions or complex continuing care needs (Carnevale, Rehm, Kirk, & McKeever, 2008), and medically complex and fragile (Gordon et al, 2007). For this study, the term medically fragile will be used to characterize adolescents who depend on respiratory technology to maintain their health.…”
Section: Introductionmentioning
confidence: 99%